Orientamenti strategici e aspetti di Brand Management nel settore vitivinicolo italiano - Lo Russo, Stefano (Piccola Impresa / Small Business, 2007)
In the last decade the global wine market has gone through substantial changes, both as for single companies and cooperatives. Wine consumption is rising in those countries which historically did not use to drink it, whereas it continues to decrease in others. The wine world market has recently been characterised by a rising trend in both demand and supply. As far as supply is concerned, recent trends confirm the more and more important role of the new strong producers (California, Chile, New Zealand) in guiding the repositioning strategies of the traditional producers (especially France, Italy, Spain and Germany). The current competition among wine companies brings small Italian producers to an increase in the quality of bottled wine, as well as a diversification of the product and an improvement of the marketing analysis instruments. This paper aims at highlighting the importance of the strategic approach expertise for Italian firms. It is important for small wine companies to focus on those marketing mix levers which are more effective with respect to the firm’s and customer’s specificity. Through a case study analysis this paper shows the role of the brand management within the marketing function and its importance for business success